Characteristics of organic fertilizer derived from fleshing waste with teak (Tectona grandis) wood scrap - Gresy Griyanitasari; Iwan Fajar Pahlawan (Majalah Kulit, Karet, dan Plastik, 2020)
The processing of leather tanning industry wastes into useful products is a one way to solve the industrial problem. This research aimed to evaluate the characteristics of organic fertilizer after the composting process of skins/hides fleshing waste with the addition of teak wood scrap as rice husk substitution. The study was an initial research to analyze the organic fertilizer, quantitatively and qualitatively. The compliance of SNI 19-7030-2004, regarding the specification of compost from organic domestic wastes, was set as the reference. Rice husk, which is commonly added in the composting process, was used as a comparison. The materials used in this study were fleshing waste, rice bran, bio-activator, rice husk, and teak wood scraps. The results showed that the organic compound, moisture, C organic, carbon, and total N content of teak wood scraps and rice husk were similar. Thus, the resulted fleshing waste-based fertilizer has similar value of macro and micro element. Through comparing the parameter quality of organic waste in the Indonesian national standard of SNI 19-7030-2004, teak wood scrap can be used as an alternative to substitute rice husk in the composting process of fleshing waste to support the sustainability of the leather tannery.